静动液辅助制动系统恒转矩制动策略研究 - 吕建刚; 郭劭琰; 李彦路; 滕飞; 宋彬 (Jixie chuandong)
A constant torque braking strategy for tracked vehicle hydrostatic and hydraulic auxiliary braking system is studied.Combining the test and theoretical analysis results,the influence law of coupler filling liquid quantity and hydraulic pump discharge variation to vehicle braking force under the hydrodynamic braking and hydrostatic braking work condition is obtained.Absorbing the advantages of hydrodynamic braking and hydrostatic braking,aiming at the work condition of hydrodynamic-hydrostatic braking,the constant torque braking strategy is built.The vehicle constant torque braking is achieved through the automatic regulation of coupler filling liquid quantity and hydraulic pump discharge.The efficiency is verified through the comparison of energy recovery and braking length before and after using constant torque braking strategy.